Human risk associated with exposure to mixtures of antiandrogenic chemicals evaluated using in vitro hazard and human biomonitoring data. (March 2023) - Ma, Yanying; Taxvig, Camilla; Rodríguez-Carrillo, Andrea; Mustieles, Vicente; Reiber, Lena; Kiesow, Anja; Löbl, Nathalie Michelle; Fernández, Mariana F.; Hansen, Tina Vicky Alstrup; Valente, Maria João; Kolossa-Gehring, Marike; David, Madlen; et al.
Graphical abstract: Graphical abstract illustrating the approach used for identifying the chemical mixture risk drivers for male reproductive health. Abstract: Background: Scientific evidence for underestimated toxicity from unintentional exposure to chemical mixtures is mounting. Yet, harmonized approaches on how to assess the actual risk of mixtures is lacking. As part of the European Joint programme 'Human Biomonitoring for Europe' we explored a novel methodology for mixture risk assessment of chemicals affecting male reproductive function. Methodology: We explored a methodology for chemical mixture risk assessment based on human in vitro data combined with human exposure data, thereby circumventing the drawbacks of using hazard data from rodents and estimated exposure intake levels. Human androgen receptor (hAR) antagonism was selected as the most important molecular initiating event linked to adverse outcomes on male reproductive health. Results: Our work identified 231 chemicals able to interfere with hAR activity. Among these were 61 finally identified as having both reliable hAR antagonist and human biomonitoring data. Calculation of risk quotients indicated that PCBs (118, 138, 157), phthalates (BBP, DBP, DIBP), benzophenone-3, PFOS, methylparaben, triclosan, some pesticides (i.e cypermethrin, β-endosulfan, methylparathion, p, p-DDE), and a PAH metabolite (1-hydroxypyrene) contributed to the mixture effect. The major chemical mixture drivers were PCB 118, BBP, PFOS, DBP, and the UV filter benzophenone-3, together contributing with 75% of the total mixture effect that was primarily driven by high exposure values. Conclusions: This viable way forward for mixture risk assessment of chemicals has the advantages of (1) being a more comprehensive mixture risk assessment also covering data-poor chemicals, and (2) including human data only. However, the approach is subjected to uncertainties in terms of in vitro to in vivo extrapolation, it is not ready for decision making, and needs further development. Still, the results indicate a concern for adverse effects on reproductive function in highly exposed boys, especially when considering additional exposure to data-poor chemicals and chemicals acting by other mechanisms of action.